Control de la actividad reproductiva en ovejas de raza Churra Galega Bragançana - efecto del momento de la administración de eCG - Correia, Teresa Montenegro (2014)
This work aimed to compare two different protocols - FGA + eCG and melatonin + FGA + eCG - commonly used to control the breeding activity in Churra Galega Bragançana ewes. The effect of time at eCG administration - 24 hours before or at sponge withdraw - was also assessed. ln March, 94 adult ewes were randomly divided in two groups: 25 received a subcutaneous implant of melatonin (18 mg) as the others 69 got no treatment (Control). Forty-live days afterward a vaginal sponge (20 mg 01 FGA) was inserted in all ewes. Sponges were removed 12 days later, Thirty-two Control ewes were injected with 500 lU of eCG 24 hours before sponge withdraw. The remaining 37 Control and all Melatonin ewes were injected with 500 lU of eCG at sponge removal FGA + eCG treatment was effective in controlling the breeding activity. Exogenous melatonin added no significant effect to FGA + eCG treatment. The injection of eCG 24 hours before sponge withdraw had no significant effect in the percentage of ewes presenting plasmatic levels of progesterone higher than 0.5 ng/ml, but decreased the percentages of ewes in estrus and pregnant and the interval between sponge withdraw and estrus detection.